Kobuviral Non-structural 3A Proteins Act as Molecular Harnesses to Hijack the Host ACBD3 Protein - Klima, Martin; Chalupska, Dominika; Różycki, Bartosz; Humpolickova, Jana; Rezabkova, Lenka; Silhan, Jan; Baumlova, Adriana; Dubánková, Anna; Boura, Evzen (Structure, 2017)
Picornaviruses are small positive-sense single-stranded RNA viruses that include many important human pathogens. Within the host cell, they replicate at specific replication sites called replication organelles. To create this membrane platform, they hijack several host factors including the acyl-CoA-binding domain-containing protein-3 (ACBD3). Here, we present a structural characterization of the molecular complexes formed by the non-structural 3A proteins from two species of the Kobuvirus genus of the Picornaviridae family and the 3A-binding domain of the host ACBD3 protein. Specifically, we present a series of crystal structures as well as a molecular dynamics simulation of the 3A:ACBD3 complex at the membrane, which reveals that the viral 3A proteins act as molecular harnesses to enslave the ACBD3 protein leading to its stabilization at target membranes. Our data provide a structural rationale for understanding how these viral-host protein complexes assemble at the atomic level and identify new potential targets for antiviral therapies.
Keywords: simulace molekulární dynamiky; Cloning, Molecular; Humans; vazebná místa; Virus Replication; konformace proteinů, alfa-helix; buněčné linie; rekombinantní proteiny; lidé; konformace proteinů, beta-řetězec; Adaptor Proteins, Signal Transducing; Membrane Proteins; Molecular Dynamics Simulation; Protein Conformation, beta-Strand; Protein Binding; Unilamellar Liposomes; Binding Sites; Protein Stability; Crystallography, X-Ray; Protein Conformation, alpha-Helical; unilamelární lipozómy; Gene Expression; aminokyselinové motivy; virové nestrukturální proteiny; replikace viru; adaptorové proteiny signální transdukční; Host-Pathogen Interactions; Protein Interaction Domains and Motifs; krystalografie rentgenová; Cell Line; stabilita proteinů; Viral Nonstructural Proteins; interakce hostitele a patogenu; exprese genu; vazba proteinů; klonování DNA; Kobuvirus; Recombinant Proteins; interakční proteinové domény a motivy; membránové proteiny; Amino Acid Motifs